Two-photon sensitized hollow Gd2O3:Eu3+ nanocomposites for real-time dual-mode imaging and monitoring of anticancer drug release. Issue 7 (9th December 2015) - Shen, Tingting; Zhang, Yu; Kirillov, Alexander M.; Cai, Huijuan; Huang, Kun; Liu, Weisheng; Tang, Yu
Abstract : New multifunctional two-photon sensitized hollow Gd2 O3 :Eu 3+ based nanocomposites were designed and assembled for the dual-mode imaging and real-time monitoring of anticancer drug release by photoluminescence and magnetic resonance imaging. Abstract : New two-photon sensitized multifunctional nanocomposites were designed for dual-mode imaging and real-time drug release monitoring by photoluminescence (PL) and magnetic resonance imaging (MRI). By drug loading based on coordination effect, PL signals of Eu 3+ and MRI signals of Gd 3+ can be stabilized and enhanced, respectively, which then display excellent linear decreases on drug release.